CO2 stripping from water through porous PVDF follow fiber membrane contactor - Mansourizadeh, Amir (Elsevier BV, 2011)
Porous polyvinylidene fluoride (PVDF) hollow fiber membranes were prepared via wet spinning process. The membranes were characterized in terms of gas permeation, wetting resistance and overall porosity, which are important parameters for gas absorption/stripping applications. CO2 stripping from water was conducted through the gas-liquid membrane contactor. The effect of different operating conditions on the CO2 stripping efficiency of the membrane was investigated. The results indicated a significant improvement in the CO2 stripping efficiency by increasing the liquid phase temperature. On the other hand, increasing the liquid flow rate resulted in a considerable decrease in the CO2 stripping flux. The maximum stripping efficiency of 32% was achieved at 60ml/min of the liquid flow rate, 60°C and 0.5×105Pa. It was found that the liquid phase temperature, the gas-liquid contact area and contact time are the key parameters for enhancement of CO2 stripping efficiency.